THE EFFECT OF ACCOUNTS RECEIVABLE TURNOVER ON FINANCIAL PERFORMANCE WITH GOOD CORPORATE GOVERNANCE AS A MODERATING VARIABLE IN MANUFACTURING COMPANIES - Selvia Dias Devitamalla; Suwandi Suwandi (Fakultas Ekonomi dan Bisnis Universitas Wijaya Putra, 2026)
With GCG as a moderating variable, this study examines the relationship between accounts receivable turnover and the financial performance of manufacturing companies listed on the Indonesia Stock Exchange (IDX). A quantitative approach was used for the 2022–2025 period, utilizing secondary data sourced from the companies’ annual reports and financial statements. A total of 108 observations were obtained through purposive sampling to test the relationship between accounts receivable turnover and performance. Data processing was conducted using SmartPLS 4.1.1 via the SEM-PLS approach, with stages including evaluation of the outer model, inner model, hypothesis testing, and GCG moderation analysis. Based on empirical findings, financial performance—proxied by ROA—is positively and significantly influenced by accounts receivable turnover. Meanwhile, the implementation of GCG through the board of directors, the audit committee, and independent commissioners tends to improve financial performance, but this effect has not yet reached a statistically significant level. The role of GCG also strengthens the influence of accounts receivable turnover on financial performance. The effectiveness of accounts receivable management can be supported through corporate governance, although its direct impact on profitability has not yet been optimally reflected in the company’s performance outcomes.